Atlantoaxial Fusion: Sixteen Years of Epidemiology, Indications, and Complications in New York State. Issue 20 (15th October 2016) - Derman, Peter B.; Lampe, Lukas P.; Lyman, Stephen; Kueper, Janina; Pan, Ting Jung; Girardi, Federico P.; Albert, Todd J.; Hughes, Alexander P.
Abstract : Study Design: A retrospective state database analysis. Objective: The aim of this study was to describe the epidemiology and complications of as well as indications for primary isolated atlantoaxial fusion. Summary of Background Data: Atlantoaxial fusion involves unique indications, techniques, and complications. There is limited epidemiologic literature focused specifically on this procedure. Methods: New York's Statewide Planning and Research Cooperative System database, an all-payer hospitalization reporting system, was queried to identify all patients undergoing primary isolated atlantoaxial fusion in the state from 1997 to 2012. Demographic and clinical data were extracted and analyzed. United States Census Bureau figures were used to calculate population-adjusted surgical rates. Results: One thousand five hundred fifty-nine patients underwent isolated primary atlantoaxial fusion during the study period. The overall population-adjusted annual surgical rate did not change significantly over time. By 2012, individuals aged ≥70 years had the highest incidence of surgery [2.37 per 100, 000 population; 95% confidence interval (95% CI) 1.68–3.07]. Medicare was the most common payer (44.0% of claims). Approximately 85% of patients had a Charlson/Deyo Comorbidity Index of zero or one. Over time, a significantly lower proportion of atlantoaxial fusions were attributable to rheumatic disease, and a significantly higher proportion were due to fracture. By 2012, management of fractures was the most common indication for C1-C2 fusion (44.1% of cases). Dysphagia or dysphonia occurred after 0.8% of cases, dural tear after 0.3%, infection after 0.5%, and seroma, hematoma, or hemorrhage after 0.5%. In-hospital mortality was 2.7%, of which 76% had fracture as the surgical indication. Conclusion: Isolated atlantoaxial fusions have been performed at a stable, low level over the past 16 years in New York. Although most of these patients are relatively healthy pre-operatively, approximately one in 10 experience an in-hospital complication and nearly 3% die in-hospital. Knowledge of these risks will hopefully spur further efforts to minimize them and allow for more accurate counseling of patients and their families. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the text